Further Exploring the Public Health Implications of the Network Scale-Up Method: Cross-Sectional Survey Study - Liwei Jing; Hongmei Yu; Qing Lu (JMIR Publications, 2024)
Abstract BackgroundThe decline in the number of new HIV infections among adults has slowed down, gradually becoming the biggest obstacle to achieving the 2030 target of ending the HIV/AIDS epidemic. Thus, a political declaration to ensure that 90% of people at high risk of HIV infection can access comprehensive prevention services was proposed by the United Nations General Assembly. Therefore, obtaining an accurate estimated size of high-risk populations is required as a prior condition to plan and implement HIV prevention services. The network scale-up method (NSUM) was recommended by the United Nations Programme on HIV/AIDS and the World Health Organization to estimate the sizes of populations at high risk of HIV infection; however, we found that the NSUM also revealed underlying population characteristics of female sex workers in addition to being used to estimate the population size. Such information on underlying population characteristics is very useful in improving the planning and implementation of HIV prevention services. This is especially relevant for people who inject drugs, where in addition to stigma and discrimination, criminalization further hinders access to HIV prevention services. ObjectiveWe aimed to conduct a further exploration of the public health implications of the NSUM by using it to estimate the population size, popularity ratio, and information transmission rate among people who inject drugs. MethodsA stratified 2-stage cluster survey of the general population and a respondent-driven sampling survey of people who inject drugs were conducted in the urban district of Taiyuan, China, in 2021. ResultsThe estimated size of the population of people who inject drugs in Taiyuan was 1241.9 (95% CI 1009.2‐1474.9), corresponding to 4.4×10−2−2−2 ConclusionsIn addition to being used to estimate the size of the population of people who inject drugs, the NSUM revealed that they have smaller-sized personal social networks while concealing their drug use, and these underlying population characteristics are extremely useful for planning appropriate service delivery approaches with the fewest barriers for people who inject drugs to access HIV prevention services. Therefore, more cost-effectiveness brings new public health implications for the NSUM, which makes it even more promising for its application.